Re-purposing Suzuki : a hybrid approach to actor training - Porter, Maria (Professor of theatre) (Routledge, 2022)
"Re-Purposing Suzuki: A Hybrid Approach to Actor Training introduces a system of text analysis that synthesizes physical, psychological, and vocal components in order to truthfully embody heightened texts and contexts. By understanding how the author has re-purposed Suzuki and other physical training methods, as well as Stanislavski, readers will gain an awareness of how to analyze a particular training method by extrapolating its key components and integrating it into a holistic, embodied approach to text analysis. The book explores a method of physical scoring via Rules of the Body and Rules of Composition, as well a method of approaching heightened texts from Greek drama to post-modern playwrights that draws on the individual actor's imagination and experience and integrates voice, mind, and body. Readers will be able to either replicate this approach, or apply the logic of its building blocks to assemble their own personal creative process applicable to a variety of performance genres. This is a source book for actors, theatre students, practitioners, and educators interested in assembling tools derived from different sources to create alternative approaches to actor training. While the process outlined in the book evolves in a classroom setting, the components of the pedagogy can also be practiced by individuals who are interested in finding new ways to explore text and character and bring them into their own personal practice"--